AB1193 Usage Pattern of Concomitant Therapy with Biological Dmards in Chinese Patients with Rheumatoid Arthritis: A Multi-Center Cross-Sectional Study. (9th June 2015) - Liu, T.; An, Y.; Li, Z.; He, D.; Wu, L.; Li, J.; Liu, Y.; Bi, L.; Zhou, B.; Lin, C.; He, L.; Liu, X.; et al.
Abstract : Background: Biological disease modifying antirheumatic drugs (bDMARDs) are frequently used in combination with other drugs. Very limited data are available on concomitant therapy with bDMARDs in China. Objectives: To investigate the usage patterns and safety of concomitant drugs in Chinese RA patients receiving bDMARDs. Methods: Patients from 15 Chinese hospitals were recruited in this cross-sectional study. Consenting patients (aged ≥18 years) diagnosed with RA receiving bDMARDs were included. Results: Data collected from 802 patients with a mean (SD) age of 49.0 (13.9) years (81.3% women) were analyzed. Among these patients, 89.5%, 56.1%, 29.7%, and 19.1% were receiving concomitant conventional DMARDs (cDMARDs), nonsteroidal anti-inflammatory drugs (NSAIDs), glucocorticoids (GC), and drugs for local application (LA drugs), respectively. In total, 718 patients were receiving concomitant cDMARDs. The proportion of patients using 1, 2, and 3 concomitant cDMARDs was 49.3%, 41.2%, and 9.5%, respectively. The most common cDMARDs were methotrexate, hydroxychloroquine, leflunomide, and sulfasalazine; used by 65.9%, 41.8%, 41.5%, and 6.3% patients at a mean (SD) daily dose (mg) of 1.4 (0.4), 340.3 (96.3), 15.4 (5.2), and 1753.3 (693.3), respectively. The respective mean (SD) duration of treatment (days) was 443.7 (845.8), 261.3 (409.4), 413.4 (578.5), and 429.1 (1039.9). Among the 238 patients on concomitant GC, 73.1% and 23.1% patients were receiving oral prednisone and methylprednisolone at a mean (SD) weekly dose (mg) of 57.8 (31.9) and 59.7 (151.6), respectively. In total, 17.6% patients reported at least one GC-associated adverse event (AE) at a mean (SD) duration of treatment (weeks) of 12 (28.3); the most common AEs were moon face (13.9%) and weight gain (4.2%). Among the 450 patients receiving concomitant NSAIDs, 43.1%, 20.2%, and 12.0% patients were receiving celecoxib, meloxicam, and loxoprofen sodium at a mean (SD) daily dose (mg) of 306.2 (100.1), 12.8 (3.5), and 143.9 (45.3), respectively. Most NSAID users were receiving NSAIDs at a dose lower than the daily maximum, except 2 patients using diclofenac acid at higher than daily maximum dose (150 mg). Only 3.6% NSAID users reported at least one AE; the most common AE was gastrointestinal discomfort (3.1%). A total of 153 patients were receiving concomitant LA drugs. The most common LA drugs were ketoprofen, diclofenac acid, and a Chinese herb medicine "Jia Wei Shuang Bai San", used by 30.1%, 20.9%, and 10.5% patients, respectively. The corresponding mean (SD) treatment duration (weeks) was 2.0 (4.1), 7.8 (26.4), and 16.9 (28.0), respectively. The predominant reason (62.9% patients) for not using LA drugs was the lack of physician-directed prescription. Conclusions: The usage patterns of concomitant cDMARDs and NSAIDs in Chinese RA patients receiving bDMARDs are similar to those in Western countries. The 17.6% concomitant GC users who reported at least one AE are receiving GC for longer time (12 weeks on average). LA drugs including traditional Chinese medicine offer a broad option for Chinese patients but are less commonly used due to lack of prescription from physicians. These findings suggest that usage patterns of concomitant GC and LA drugs might still need to be optimized for Chinese RA patients receiving bDMARDs. Acknowledgements: This study was sponsored by Shanghai Roche Pharmaceuticals Limited. Disclosure of Interest: None declared